EFECTO DE LA TEMPERATURA Y PRESIÓN DE TERMOHIDRÓLISIS SOBRE LA DESFIBRILACIÓN DE RASTROJO DE PODA DE VID (VITIS VINÍFERA) PARA SU EMPLEO EN DIGESTIÓN ANAERÓBICA SECA - Jorge Zegarra-Paredes (2021)
The objective of the research was to determine the effect of temperature and pressure on defibrillation in grapevine pruning residues for the production of biogas in a high-efficiency anaerobic biodigester. Laboratory tests were carried out in a thermohydrolyzer designed to evaluate steam explosion thermohydrolysis and determine the effect of temperature and pressure on the defibrillation of residues from vine pruning. Subsequently, the biogas production and methane productivity were evaluated in high-efficiency reactors, according to the German standard VDI 4630, quantified based on three hydraulic residence times at 5, 10 and 15 days and with a fixed concentration of solids. at 10%. The results found show a significant effect (p <0.05) in cell rupture at a temperature of 80 ° C, however the effect of pressure was not significant (p> 0.05). Regarding the production of biogas, there was a production of 210 ml of methane in thermohydrolyzed vine brush compared to 96 ml of methane in non-thermohydrolyzed brush, with significant differences between the two (p <0.05) substrates ... In conclusion, it has been determined that the best response to thermohydrolysis in vine brush it was obtained as a function of temperature and not pressure in the process. Finally, it is concluded that the thermohydrolyzed vine chaff had a production of 40.35% more methane than the non-thermohydrolyzed one, demonstrating the greater effectiveness of the process.